2018
DOI: 10.1364/ao.57.001417
|View full text |Cite
|
Sign up to set email alerts
|

Air wedge with variable refractive index for precise laser beam steering in a small range

Abstract: This paper provides the results of work on a new method for metrological laser beam steering for the purpose of angular stabilization. Frequency stabilized metrological lasers are used for interference measurements of length and angle. Angular deviation of the beam may cause cosine errors when measuring displacements. This paper presents a method for metrological laser beam deflection with an air wedge of variable refractive index. The change in the index is achieved by changing the air pressure in the wedge v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This small deflection is enough to realize interferometric measurement by changing the interference fringe. The state-of-art interferometry, which proposed for the ultra precise measurement of the small laser angular deflection, can provide the resolution on the single nrad-level and extremely robust and insensitive to the most common disturbances [42,43].…”
Section: Exploration Of Quantum Vacuum Properties Using Ultraintense ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This small deflection is enough to realize interferometric measurement by changing the interference fringe. The state-of-art interferometry, which proposed for the ultra precise measurement of the small laser angular deflection, can provide the resolution on the single nrad-level and extremely robust and insensitive to the most common disturbances [42,43].…”
Section: Exploration Of Quantum Vacuum Properties Using Ultraintense ...mentioning
confidence: 99%
“…Meanwhile, one may anticipate that the vacuum refraction is also one of the basic and critical effects of this vacuum medium [41]. Additionally, it provides an alternative method for detecting quantum vacuums as the precision of beam angle measurements advances to the nano-radian scale and further [42,43]. Some early attempts to study vacuum refraction signals can be found in [44,45].…”
Section: Introductionmentioning
confidence: 99%